MICA/B-targeted antibody promotes NK cell–driven tumor immunity in patients with intrahepatic cholangiocarcinoma. (31st December 2022) - Oliviero, Barbara; Varchetta, Stefania; Mele, Dalila; Pessino, Greta; Maiello, Roberta; Falleni, Monica; Tosi, Delfina; Donadon, Matteo; Soldani, Cristiana; Franceschini, Barbara; Torzilli, Guido; Piccolo, Gaetano; et al.
ABSTRACT: The major histocompatibility complex-class I chain related proteins A and B (MICA/B) is upregulated because of cellular stress and MICA/B shedding by cancer cells causes escape from NKG2D recognition favoring the emergence of cancers. Cholangiocarcinoma (CCA) is a relatively rare, though increasingly prevalent, primary liver cancer characterized by a late clinical presentation and a dismal prognosis. We explored the NKG2D-MICA/B axis in NK cells from 41 patients with intrahepatic cholangiocarcinoma (iCCA). The MICA/B-specific 7C6 mAb was used for ex vivo antibody-dependent cytotoxicity (ADCC) experiments using circulating, non tumor liver- and tumor-infiltrating NK cells against the HuCCT-1 cell line and patient-derived primary iCCA cells as targets. MICA/B were more expressed in iCCA than in non-tumoral tissue, MICA transcription being higher in moderately-differentiated compared with poorly-differentiated cancer. Serum MICA was elevated in iCCA patients in line with higher expression of ADAM10 and ADAM17 that are responsible for proteolytic release of MICA/B from tumor. Addition of 7C6 significantly boosted peripheral, liver- and tumor-infiltrating-NK cell degranulation and IFNγ production toward MICA/B-expressing established cell lines and autologous iCCA patient target cells. Our data show that anti-MICA/B drives NK cell anti-tumor activity, and provide preclinical evidence in support of 7C6 as a potential immunotherapeutic tool for iCCA.